The effectiveness of Waqaf An-Nur Corporation Berhad / Mohammad Firdaus Md Nawai and Fatin Nabihahusna Nordin - Md Nawai, Mohammad Firdaus; Nordin, Fatin Nabihahusna (Faculty of Business and Management, 2014)
The study is conducted as a partial fulfilment of the coursework of project paper (BM220). Title of “The effectiveness of Waqaf An-Nur Corporation Berhad”. The main objective of the study is to determine at what point Waqaf An-Nur Corporation Berhad give an effectiveness on the activities that the company involved to help person those in need. The purpose of this study was to investigate the effectiveness of the selected independent variables which are reliability, responsiveness and empathy. The data were collected from 30 respondents using questionnaire. Then the results were analyzed by using SPSS to find the significant relationship with the dependent variables.